Isometric Mid-thigh Pull Kinetics: Sex Differences and Response to Whole-Body Vibration. Issue 9 (September 2020) - Merrigan, Justin J.; Dabbs, Nicole C.; Jones, Margaret T.
Abstract : Abstract: Merrigan, JJ, Dabbs, NC, and Jones, MT. Isometric mid-thigh pull kinetics: Sex differences and response to whole-body vibration. J Strength Cond Res 34(9): 2407–2411, 2020—The purpose was to investigate whether whole-body vibration's (WBV's) effect on force-time characteristics is dependent on time and sex. Subjects (men, n = 18; women, n = 18) performed a static quarter squat with WBV (frequency: 30 Hz; amplitude: 2–4 mm) and without for 5 × 30 seconds repetitions (1:1, WBV:rest). Next, they performed 2 sets of 3 repetitions of the isometric mid-thigh pull (IMTP) with 3 minutes of intraset rest and 5 minutes of interset rest. Peak force (PF) and rate of force development (RFD) from 0 to 50, 0 to 150, and 0 to 250 milliseconds (RFD50, RFD150, and RFD250) were analyzed ( p < 0.05). A significant effect of condition existed for PF ( p = 0.019) and RFD from 0 to 250 seconds ( p = 0.031). In women, RFD was moderately affected immediately post-WBV ( p = 0.070; d = 0.49). Yet in men, the effect of WBV on RFD existed 15 minutes after exposure ( p = 0.017; d = 0.36). In absolute terms men produced more PF than women (1, 008.6 ± 289.7 N; p < 0.001). All RFD bands were greater in men than those of women (RFD50, 5, 519.3 ± 2, 927.2 N·s −1 ; RFD150, 3, 361.4 ± 1, 385.3 N·s −1 ; RFD250, 2, 505.7 ± 867.1 N·s −1 ; p < 0.05). However, relative to fat-free mass, PF in men (40.1 ± 7.2 N·kg −1 ) was not different from women (37.7 ± 6.4 N·kg −1 ; p = 0.284). The same was true for RFD150 (21.1 ± 24.1 N·kg −1 ·s −1 ; p = 0.084) and RFD250 (10.9 ± 14.1 N·kg −1 ·s −1 ; p = 0.128). Yet, RFD50 remained greater in men (139.1 ± 33.6 N·kg −1 ·s −1 ) than that of women (86.8 ± 34.5 N·kg −1 ·s −1 ; p = 0.034). Current WBV protocols resulted in trivial to moderate effects on IMTP forces, which may be dependent on sex and time. Finally, it is recommended that women complete movements with the intent to move weight quickly to improve early RFD.